Investigating Junior High School Students' Perceptions Of Using Canva As A Media For Writing Recount Texts - Nasution, Nurul Oktari; Dewi, Utami; Dalimunthe, Ahmad Amin (CV. ITTC INDONESIA, 2024)
This study investigates how eighth-graders at Nurul Ilmi Integrated Islamic Junior High School feel about using Canva to create recount text media. This study, which took place in the academic year 2023–2024, included 22 participants who used Canva in their English classes. The study examines at the difficulties and shortcomings that students have when writing in English. Utilizing a qualitative approach with phenomenological types, the research methodology focuses on the students' actual experiences. Both questionnaires and interviews, which are descriptive qualitative methods, were used to gather data. The results show that students have a positive view of Canva, believing it to be easy to use, beneficial in streamlining the writing process, and successful in illustrating story ideas. Although there are certain obstacles, like problems choosing a typeface, students acknowledge that Canva has a big influence on their writing and creativity. Canva is a useful tool for improving students' narrative retelling skills and encouraging successful communication in the digital age, according to the study's conclusion. Future research should look into qualitative investigations, comparative analyses with other digital tools, longitudinal studies, and teacher perspectives on incorporating Canva into writing instruction. This study researched by students of the Department of English Education, Faculty of Tarbiyah and Keguruan, State Islamic University of North Sumatra adds to our knowledge of technology-enhanced learning in writing instruction and highlights Canva's potential in helping students write better retelling texts.